Validation of the Dyspnoea-12 and Multidimensional Dyspnea profile among older Swedish men in the population - Max Olsson; Magnus Ekström (BMC Geriatrics, 2022)
Abstract Background The Dyspnoea-12 (D12) and Multidimensional dyspnea profile (MDP) are commonly used instruments for assessing multiple dimensions of breathlessness but have not been validated in older people in the population. The aim of this study was to validate the D12 and MDP in 73-years old men in terms of the instruments’ underlying factor structures, internal consistency, and validity. Methods A postal survey was sent out to a population sample of 73-years old men (n = 1,193) in southern Sweden. The two-factor structures were evaluated with confirmatory factor analysis, internal consistency with Cronbach's alpha, and validity using Pearson´s correlations with validated scales of breathlessness, anxiety, depression, fatigue, physical/mental quality of life, body mass index (BMI), and cardiorespiratory disease. Results A total 684 men were included. Respiratory and cardiovascular disease were reported by 17% and 38%, respectively. For D12 and MDP, the proposed two-factor structure was not fully confirmed in this population. Internal consistency was excellent for all D12 and MDP domain scores (Cronbach's alpha scores > 0.92), and the instruments’ domains showed concurrent validity with other breathlessness scales, and discriminant validity with anxiety, depression, physical/mental quality of life, BMI, and cardiorespiratory disease. Conclusions In a population sample of 73-years old men, the D12 and MDP had good psychometrical properties in terms of reliability and validity, which supports that the instruments are valid for use in population studies of older men.